Spectator Awareness and Support of Safety and Security Practices and Technologies during COVID-19 - Stacey A. Hall; Joslyn Zale; Ryan Kavanaugh (Journal of Applied Sports Management, 2023)
Since 2020, a global pandemic has challenged the sports industry in unprecedented ways; the industry came to a standstill at one point, eventually returning with limited capacities and public health safety and security precautions. This exploratory study examined spectators' awareness and level of support for general safety and security measures and their willingness to embrace COVID-19-specific policies as they returned to live events in the U.S. in 2021. A total of 609 participants who attended a professional or collegiate sporting event within the previous three years completed the survey. Results indicated that spectators considered security measures when deciding to attend events and preferred visible measures (e.g., law enforcement presence, screening technologies, and security cameras). Spectators were willing to encounter COVID-related measures (e.g., temperature checks, digital health passes, and touchless screening) to return to live events. The most important decision-making factor in future event attendance was enhanced venue/event cleaning/hygiene protocols.
Keywords: COVID-19; safety and security policies and procedures; spectator experience; return to play; fan perceptions